Hubungan Efikasi Diri Dan Iklim Organisasi Terhadap Kinerja Staf Tenaga Kependidikan Universitas Muhammadiyah Surakarta - Husnawati, Reny, Dr. Moordiningsih, M.Si, Psi, Achmad Dwityanto, S.Psi, M.Si (2016)
The existence of administrative employee at muhammadiyah university of Surakarta (UMS) is the spearheading provision of administrative services for the academic community and others UMS stakeholder. However, the performance of administrative staff at UMS generally show that has not been optimal. This reseach objective is to examine the influence of self efficacy and organizational climate on performance of administrative staff at UMS. This reseach using quantitative approach. The populations are administrative staffs at UMS that spread across units in the muhammadiyah university of Surakarta (UMS). The samples are 175 and using quota random sampling. The data was collected by a questionnaire instrument. The sampling technique used simple random sampling. Techniques of data analysis using multiple linear regression analysis with SPSS 17.00. The results shown that the major and minor hypothesis was accepted. Organizational climate and self efficacy have a positive and significant influence to the performance of administrative staff at UMS, either it self or together. It means that as good as the organizational climate and high of self efficacy is, the performance also be good and vice versa. So, organizational climate and self efficacy are significant factors to increase performance. Which organizational climate had a dominant impact to increase administrative staff's performance at UMS.